HUBUNGAN KEKUATAN OTOT TUNGKAI DAN KOORDINASI MATA-KAKI DENGAN AKURASI DALAM MELAKUKAN SHOOTING PADA TIM SSB (U,16) CHEVRON PEKANBARU - kurniawan, Igun kurniawan; Agust, Kristi Agust; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The problems in this research started from the observed that writer found in field and the writer also did the interview with coach of SBB team Chevron Pekanbaru, Mr. Sukirman. The writer found the deficiency during in doing shooting when match in BATERAI R. The physical condition is not well in leg muscle and ankle coordination when doing shooting, so the result of the shooting was not maximum. The purpose of this research was to know the relationship between leg muscle power and ankle coordination with accuration in doing shooting of SBB team (u,16) in chevron pekanbaru. The population of this research was SBB team (U,16) amount 16 peoples. This research only used one team as a population. Because of the total of the team was a bit so the writer took a lot of people in this team as a sample. The writer used total sampling technique in took the sample. To got the data, this research used Leg Dynamometer test for leg muscle power, test in kicking the ball to the wall in diameter 65 cm, the high was 1,24 m, and distance from the line start 2 m for ankle coordination, and test in kicking the ball to the target was 76 cm the point was 7 (seven), 90 cm the point was 5 (five), 103 cm the point was 3 (three) and 185 cm the point was 1 (one). Then, the distance to the target from line start 16,5 m for accuration in doing shooting. Then, the data analysis the writer used was simple correlation product moment. Based on the analysis writer got the data, correlation X1 with Y in the amount of  rhitung = 0,004>rtabel =0,514 and X2 with Y in the amount of rhitung = 0,086>rtabel =0,514, meanwhile X1 and X2 with Y rhitung = 0,086>rtabel =0,514. Because of overall have not relationship that show in data analysis, so Ha was rejected and Ho accepted. The meaning was there were not a relationship between leg muscle power and ankle coordination with accuration in doing shooting of SBB team (u,16) in chevron pekanbaru. Thus, the provision of correlation to correlation and  variable to other  variable fixed from rhitung >rtabel. Key words: leg muscle power, ankle coordination, accuration in doing shooting